Silencing mitogen-activated protein kinase-activated protein kinase-2 arrests inflammatory bone loss - Li, Qiyan; Yu, Hong; Zinna, Robert; Martin, Kylie; Herbert, Betthany; Liu, Angen; Rossa Júnior, Carlos [UNESP]; Kirkwood, Keith L. (Elsevier, 2011)
p38 mitogen-activated protein kinases (MAPKs) are critical for innate immune signaling and subsequent cytokine expression in periodontal inflammation and bone destruction. In fact, previous studies show that systemic p38 MAPK inhibitors block periodontal disease progression. However, development of p38 MAPK inhibitors with favorable toxicological profiles is difficult. Here, we report our findings regarding the contribution of the downstream p38 MAPK substrate, mitogen-activated protein kinase-activated protein kinase 2 (MK2 or MAPKAPK-2), in immune response modulation in an experimental model of pathogen-derived lipopolysaccharide (LPS)-induced periodontal bone loss. To determine whether small interfering RNA (siRNA) technology has intraoral applications, we initially validated MK2 siRNA specificity. Then, gingival tissue surrounding maxillary molars of rats was injected with MK2 siRNA or scrambled siRNA at the palatal regions of bone loss. Intraoral tissues treated with MK2 siRNA had significantly less MK2 mRNA expression compared with scrambled siRNA-treated tissues. MK2 siRNA delivery arrested LPS-induced inflammatory bone loss, decreased inflammatory infiltrate, and decreased osteoclastogenesis. This proof-of-concept study suggests a novel target using an intraoral RNA interference strategy to control periodontal inflammation.
Keywords: Innate immunity; Cell signaling; Bone resorption; RANKL; Immunology